A Secret of Birds & Bone Enchants with its magic realism and originality. - Hargrave, Kiran Millwood
In an Italian city ravaged by plague, Sofia's mother carves beautiful mementoes from bones. But one day, she doesn't return home. Did her work lead her into danger? Sofia and her little brother Ermin are sent to the convent orphanage but soon escape, led by an enigmatic new friend and their pet crow, Corvith. Together they cross the city underground, following clues in bones up to the towers of Siena, where circled by magpies the children find the terrible truth...
Keywords: English-Fiction